2002
DOI: 10.1053/jhep.2002.34343
|View full text |Cite
|
Sign up to set email alerts
|

Effects of noradrenalin and albumin in patients with type I hepatorenal syndrome: A pilot study

Abstract: Treatment of hepatorenal syndromes (HRSs) is currently based on vasopressin analogs. The aim of this pilot study was to evaluate the efficacy and safety of noradrenalin (NA) in the treatment of type 1 HRS. Between 1998 and 2000, 12 consecutive patients with type 1 HRS (7 men, 5 women; mean age, 54 ؎ 11 years; mean Child-Pugh score, 11.3 ؎ 1.7) were treated with intravenous NA (0.5-3 mg/h), in combination with intravenous albumin and furosemide. NA was given for 10 ؎ 3 days, at a mean dose of 0.8 ؎ 0.3 mg/h. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
200
1
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 331 publications
(210 citation statements)
references
References 20 publications
4
200
1
5
Order By: Relevance
“…Patients who were treated with vasopressin had a significantly higher HRS recovery rate and improved survival and were more likely to receive a liver transplant (100). Finally, the administration of intravenous norepinephrine in association with albumin and furosemide resulted in reversal of HRS in 10 (83%) of 12 patients with type 1 HRS, and ischemic episodes were observed in only two (104). It is interesting that two of the responders to norepinephrine had previously failed terlipressin therapy.…”
Section: Pharmacologic Treatmentmentioning
confidence: 99%
“…Patients who were treated with vasopressin had a significantly higher HRS recovery rate and improved survival and were more likely to receive a liver transplant (100). Finally, the administration of intravenous norepinephrine in association with albumin and furosemide resulted in reversal of HRS in 10 (83%) of 12 patients with type 1 HRS, and ischemic episodes were observed in only two (104). It is interesting that two of the responders to norepinephrine had previously failed terlipressin therapy.…”
Section: Pharmacologic Treatmentmentioning
confidence: 99%
“…The pathogenesis of renal changes in hepatorenal syndrome is starting to be understood, and a novel therapy using vasoconstrictors in preliminary clinical trials appears promising. 1,2 Hepatopulmonary syndrome with intrapulmonary shunts and hypoxia in patients with portal hypertension also is well described, but less well understood. 3 These stand as just two examples of how otherwise healthy organs remote from the liver can be adversely affected in the face of cirrhosis and portal hypertension.…”
Section: Commentsmentioning
confidence: 99%
“…One small pilot study (N=12) looked at the effect of norepinephrine and found norepinephrine effective. 2 One study found that norepinephrine had similar outcomes compared to terlipressin 3 . However, the use of norepinephrine on general medical wards is usually not possible, and therefore was not an option for our patient.…”
Section: Literature Reviewmentioning
confidence: 99%